Microstructural Evolution of a Selective Laser Melted FeCoCrNiMn–(N,Si) High‐Entropy Alloy Subject to Cold‐Rolling and Subsequent Annealing - Zhang, Zhonglun; Wu, Yufan; Gu, Ji; Song, Min (Advanced engineering materials, 2023)
Herein this article, selective laser melting (SLM) technique is used to manufacture N and Si contained FeCoCrNiMn high‐entropy alloy (HEA). The SLMed FeCoCrNiMn–(N,Si) alloy is then treated by cold‐rolling and isochronous annealing. The influences of Si and N additions on the microstructural evolution and tensile properties of the HEA are investigated. It is shown that adding Si and N elements increases the recrystallization temperature and postpones the whole recrystallization processing of the alloy. The annealing‐induced anomalous hardening is seen for the alloy at both 500 and 600 °C. When the annealing treatment temperature is 800 °C and above, the alloy is fully recrystallized in 1 h. The tensile properties evolution of the FeCoCrNiMn–(N,Si) alloy with annealing temperature has the similar tendency to the equiatomic FeCoCrNiMn alloy. In addition, uniformly distributed Cr2N particles form during the annealing processing. The dispersion and small size of the Cr2N particles significantly improve the tensile mechanical properties of the alloy by inhibiting the movements of both dislocations and grain boundaries. The additions of minor Si and N elements increase the recrystallization temperature and postpone the recrystallization processing of selective laser melted FeCoCrNiMn high‐entropy alloy. The formation of uniformly distributed small Cr2N particles during the annealing processing significantly improves the tensile mechanical properties of the alloy by inhibiting the movements of both dislocations and grain boundaries.